2004
DOI: 10.1097/00005537-200406000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Difluoromethylornithine‐Induced Reversible Hearing Loss Across a Wide Frequency Range

Abstract: An 18-day regimen of 750 mg/kg per day of DFMO given subcutaneously in neonatal gerbils causes minimal side effects with broad-frequency HL that, after 3 weeks of recovery, is fully reversible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…These side effects are not observed at lower doses of DFMO (26,27). Ototoxicity has been demonstrated to occur in experimental animals treated with DFMO including rats (35), guinea pigs (36), gerbils (37), and mice (38). Using immunohistochemistry, a high level of ornithine decarboxylase was observed in the inner ear of the rat, with the highest in the organ of Corti and lateral wall followed by the cochlear nerve (39).…”
mentioning
confidence: 99%
“…These side effects are not observed at lower doses of DFMO (26,27). Ototoxicity has been demonstrated to occur in experimental animals treated with DFMO including rats (35), guinea pigs (36), gerbils (37), and mice (38). Using immunohistochemistry, a high level of ornithine decarboxylase was observed in the inner ear of the rat, with the highest in the organ of Corti and lateral wall followed by the cochlear nerve (39).…”
mentioning
confidence: 99%
“…Although these numbers were not significant, it is plausible that DFMO does affect the higher frequency region of the cochlea (base) with greater capacity than the lower frequencies given the increased threshold shift observed in this region. Animal studies support this observation, where DFMO toxicity has been reported to affect the basal high‐frequency region of the cochlea most 35–37 . Collectively, average threshold shifts were greater in the experimental group relative to the control group across the frequency range; however, additional investigation with a larger study population is warranted to determine the extent of this threshold shift.…”
Section: Discussionmentioning
confidence: 65%
“…Animal studies support this observation, where DFMO toxicity has been reported to affect the basal highfrequency region of the cochlea most. [35][36][37] Collectively, average threshold shifts were greater in the experimental group relative to the control group across the frequency range; however, additional investigation with a larger study population is warranted to determine the extent of this threshold shift. Sufficient data were available for 250 participants to carry out statistical analysis; 117 in the DFMO group and 133 in the placebo group.…”
Section: Discussionmentioning
confidence: 93%
“…Another possible mechanism for the vestibular toxicity is damage to vestibular hair cells. DFMO has long been known to damage cochlear hair cells leading to reversible hearing loss in all species 21 . In human clinical trials using doses of DFMO comparable to those used in this study, hearing loss is common and may be incomplete or fluctuate over time 22 .…”
Section: Discussionmentioning
confidence: 88%